2018
DOI: 10.3390/v10060294
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Viral and Host Factors in Chikungunya Virus Infection: Targets for Antiviral Strategies

Abstract: Chikungunya virus (CHIKV) has re-emerged as one of the many medically important arboviruses that have spread rampantly across the world in the past decade. Infected patients come down with acute fever and rashes, and a portion of them suffer from both acute and chronic arthralgia. Currently, there are no targeted therapeutics against this debilitating virus. One approach to develop potential therapeutics is by understanding the viral-host interactions. However, to date, there has been limited research undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 271 publications
(365 reference statements)
0
32
0
Order By: Relevance
“…Moreover, it has been reported to have an antiviral role in infection with HIV and some flaviviruses [19,66]. Recently, a KAT5 inhibitor was shown to have an inhibitory effect against the Chikungunya virus, at the step of viral replication with a therapeutic index of 4.65 [19], and against HCV [20,23].…”
Section: Human Protein Target Annotationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been reported to have an antiviral role in infection with HIV and some flaviviruses [19,66]. Recently, a KAT5 inhibitor was shown to have an inhibitory effect against the Chikungunya virus, at the step of viral replication with a therapeutic index of 4.65 [19], and against HCV [20,23].…”
Section: Human Protein Target Annotationmentioning
confidence: 99%
“…The liquid from a cashew nutshell (Anacardium occidentale) consists of various phenolic lipid compounds, including anacardic acid, cardol, and cardanol. Previous reports suggested that their biological activities include anti-oxidant, anti-cancer, anti-inflammation, anti-microbial and anti-viral properties [19][20][21][22][23]. Mixed anacardic acid was demonstrated to have potential compound to inhibit Hepatitis C virus (HCV) life cycle [23], and may act through perturbation of the host target at lysine acetyltransferase 5 (KAT5 or TIP60), which is involved in viral replication [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nsP1 protein is a viral mRNA capping enzyme with both methyltransferase and guanylyltransferase (GTase) activities. The protein is responsible for capping and methylation of new synthesized viral RNA protecting it from degradation by host exonucleases and directing efficient translation of viral mRNAs (Rupp et al 2015;Wong and Chu 2018). Additionally, nsP1 plays an important role in RC formation and localization, which is directed by an alpha-helical amphipathic loop and palmitoylation site that allows nsP1 containing RCs to dock to the host cell plasma membrane.…”
Section: Nsp1mentioning
confidence: 99%
“…(2) nucleotide triphosphatase (NTPase) activity; (3) RNA 5′ triphosphatase activity; and (4) papain-like cysteine protease activity (Rupp et al 2015;Wong and Chu 2018;Das et al 2014b;Karpe et al 2011;Ramakrishnan et al 2017). Activity of the C-terminal protease domain is responsible for processing the viral nsP1234 polyprotein (Ramakrishnan et al 2017).…”
Section: Nsp2mentioning
confidence: 99%